Short-term outcomes of implanting a retropupillary iris-claw intraocular lens in patients with lens and intraocular lens drops - Kurniawan, Chalid; Kartasasmita, Arief S.; Harley, Ohisa (Narra J, 2024)
Lens drop and intraocular lens (IOL) drop can occur after cataract or phacoemulsification surgery, where the IOL is dislocated from the capsular bag into the vitreous cavity. The aim of this study was to investigate the short-term outcomes of implanting a retropupillary iris claw in patients with IOL drop and lens drop after phacoemulsification. A cross-sectional study was conducted at Santosa Hospital, Bandung, West Java, Indonesia, from January 2020 to December 2023. Patients were divided into two groups: IOL drop and lens drop groups. Total sampling was used, involving 51 patients in the present study, with 27 patients in the IOL drop group and 24 patients in the lens drop group. Data collected included age, sex, eye laterality, the onset of IOL drop or lens drop, intraocular pressure (IOP), uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), record of astigmatism change preoperative and postoperative, and postoperative pars plana vitrectomy (PPV) complications. Our data indicated that the UDVA significantly improved in both IOL drop and lens drop groups after PPV surgery (p<0.001). However, there were no significant changes in IOP or astigmatism following the surgery in either group. Over one month, both groups showed improved UDVA, decreased IOP, and changes in astigmatism, with no significant differences between groups. Similarly, there was no significant difference in CDVA between IOL drop and lens drop groups. Only four complications were recorded in the present study. Comparing IOL drop and lens drop groups, only an increase in IOP showed a significant difference (p=0.018). Corneal edema, IOL decentration, and pupil ovalization were not significantly different. In conclusion, retropupillary iris-claw IOL implantation is safe and effective for aphakic patients with complications from phacoemulsification, regardless of whether it is lens drop or IOL drop.